EEG signatures at the transition between conscious and unconscious state during induction of general anesthesia with remifentanil and propofol - Ferreira, Ana Isabel Leitão (2021)
The precise identification of the moment of Loss Of Consciousness (LOC) during the induction phase of general anesthesia is of extreme importance for the individualization of drug doses. In the lack of an objective method to assess this moment, the development of a new methodology is needed. In this observational study, Electroencephalogram (EEG) signatures that were associated with the moment of LOC are examined as a starting point, so as to create a robust model for tracking the dynamic changes between conscious and unconscious states. The data from 12 patients under general anesthesia for neurosurgical procedures with remifentanil and propofol, are used is this study. Multitaper spectrograms were computed to observe the dynamics of EEG oscillations before and after LOC. At LOC, a decrease in gamma power and an increase in delta and alpha bands were identified.